2014
DOI: 10.1177/1098612x14530121
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and prognostic indicators in 20 cats with surgically treated primary lung tumors

Abstract: The purpose of this retrospective study of 20 client-owned cats was to describe the clinical signs, surgical interventions, histological features, stage and treatments of primary lung tumors removed by surgical excision, and to determine which factors significantly influence survival. Any cat that underwent surgical resection of a primary lung tumor between 2000 and 2007 was included in the study. Patient records were reviewed and signalment, clinical signs, preoperative diagnostics, surgical findings and hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 23 publications
1
27
0
4
Order By: Relevance
“…Thoracic lymph nodes were identified inconsistently in the present study with cranial mediastinal lymph nodes identified more commonly than tracheobronchial lymph nodes. Computed tomography has been shown to have a high specificity and sensitivity for identifying tracheobronchial lymph nodes in dogs, and size and contrast enhancement of the lymph nodes has been correlated with metastatic neoplasia or granulomatous disease . Unfortunately, histopathology of lymph nodes was uncommonly performed in the cats in this study, limiting our ability to evaluate if such a correlation between size and contrast enhancement also exists in cats.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Thoracic lymph nodes were identified inconsistently in the present study with cranial mediastinal lymph nodes identified more commonly than tracheobronchial lymph nodes. Computed tomography has been shown to have a high specificity and sensitivity for identifying tracheobronchial lymph nodes in dogs, and size and contrast enhancement of the lymph nodes has been correlated with metastatic neoplasia or granulomatous disease . Unfortunately, histopathology of lymph nodes was uncommonly performed in the cats in this study, limiting our ability to evaluate if such a correlation between size and contrast enhancement also exists in cats.…”
Section: Discussionmentioning
confidence: 85%
“…No information about cytology results of pre‐CT thoracocentesis was collected, but effusion in these cats may have been secondary to carcinomatosis, hemorrhage, lymphatic obstruction, or secondary inflammation. Pleural effusion has been reported to be a negative prognostic factor for survival after surgery . Two of the 17 cats with pleural effusion also had a pneumothorax, which may have been secondary to thoracocentesis or from mass rupture .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsere beiden Patienten wiesen ein primäres pulmonales Adenokarzinom auf, das Literaturangaben zufolge die am häufigsten diagnostizierte Lungenneoplasie der Katze darstellt (1,6,13). Die Literaturrecherche ergab nur drei weitere Studien, die bei insgesamt acht Katzen über eine Neoplasie als Ursache eines SP berichteten (10,11,15).…”
Section: Literaturunclassified
“…Die Prognose ist äußerst vorsichtig bis infaust. Maritato et al (13) operierten 20 Katzen mit einem primären Lungentumor. Die 16 Katzen, bei denen klinische Symptome aufgetreten waren, hatten eine mediane Überlebenszeit von nur 4 Tagen.…”
Section: Literaturunclassified